Application of the Advanced 2D Multi-electrode Electrical Exploration Method in Surveying Dyke’s Current Condition and Its Contribution to Assessing the Stability of Dyke - Chung, Do Anh; Minh, Vu Duc (VNU Journal of Science: Natural Sciences and Technology, 2019)
One of the important issues in assessing dykes’ stability is to survey and assess their current condition. This article introduces some new results obtained from the applying of the Advanced 2D Multi-electrode Electrical Exploration method in surveying the current condition of the Red River dyke in Hanoi, the Cau River dyke and the Thai Binh River dyke in Bac Ninh province. Comparing the survey results of the Advanced 2D Multi-electrode Electrical Exploration method with those of the drilling method shows similar layering results. However, it is very difficult to identify objects that cause instability in the body and foundation of dyke (seepage caused by sand lens, mud pit inside dyke’s foundation…) using drilling and sampling method, while these objects can be identified by the Advanced 2D Multi-electrode Electrical Exploration method. Therefore, instead of the traditional surveying method, it is highly possible to apply the Advanced 2D Multi-electrode Electrical Exploration method in surveying the current condition of dykes to contribute to the assessing of the stability of dyke sections to add into and complete the database on dykes for efficient management and maintenance of dykes. Keywords Fractures, determining seepage, heterogeneous, Advanced 2D Multi-electrode Exploration. References [1] Vu Duc Minh, Do Anh Chung, Introduction to the Advanced Multi-electrode Electrical Sounding method, VNU. Journal of Mathematics-Physics. 31(2015) 1-14. [2] Vu Duc Minh, Do Anh Chung, Perfecting the Advanced Multi-electrode Electrical Sounding method, VNU. Journal of Mathematics-Physics, 34 (2018), 90-103. https//doi.org/ 10.25073/2588-1124/vnumap.4291.